2018
DOI: 10.1016/j.nicl.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

White matter network topology relates to cognitive flexibility and cumulative neurological risk in adult survivors of pediatric brain tumors

Abstract: Adult survivors of pediatric brain tumors exhibit deficits in executive functioning. Given that brain tumors and medical treatments for brain tumors result in disruptions to white matter, a network analysis was used to explore the topological properties of white matter networks. This study used diffusion tensor imaging and deterministic tractography in 38 adult survivors of pediatric brain tumors (mean age in years = 23.11 (SD = 4.96), 54% female, mean years post diagnosis = 14.09 (SD = 6.19)) and 38 healthy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 87 publications
(101 reference statements)
2
29
1
Order By: Relevance
“…The NPS is associated with cognitive outcomes over and above individual risk factors, suggesting that the cumulative examination of risk factors can better characterize the heterogeneity in survivors' long-term outcomes (Kautiainen, Na, & King, 2019;King & Na, 2016;Micklewright et al, 2008;Papazoglou, King, Morris, & Krawiecki, 2008;Taiwo, Na, & King, 2017). Prior research has demonstrated that the NPS is related to core cognitive abilities, executive function, and functional outcomes in pediatric brain tumor survivors (King & Na, 2016;McCurdy, Rane, Daly, & Jacobson, 2016;Na et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The NPS is associated with cognitive outcomes over and above individual risk factors, suggesting that the cumulative examination of risk factors can better characterize the heterogeneity in survivors' long-term outcomes (Kautiainen, Na, & King, 2019;King & Na, 2016;Micklewright et al, 2008;Papazoglou, King, Morris, & Krawiecki, 2008;Taiwo, Na, & King, 2017). Prior research has demonstrated that the NPS is related to core cognitive abilities, executive function, and functional outcomes in pediatric brain tumor survivors (King & Na, 2016;McCurdy, Rane, Daly, & Jacobson, 2016;Na et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The neural mechanism for this association is not well known (Bells et al, 2017;Glass et al, 2017), but an association between altered white matter microstructure, in the form of reduced neural synchronization, and functioning has been found in brain tumor patients (Bells et al, 2017). Furthermore, suboptimal integration and segregation of white matter networks correlate with executive functioning impairments (Na et al, 2018).…”
Section: Treatmentmentioning
confidence: 99%
“…In line with this, focus has shifted from survival only to also include quality of life post-treatment. This shift has brought with it an increased focus on the late effects survivors may experience (Na et al, 2018), as survival comes at a cost for children with MB and CNS-PNET. They experience cognitive impairments, academic and social challenges, hearing loss, epileptic seizures, endocrine insufficiency, secondary neoplasm, stroke, and problems with balance and coordination (Benesch et al, 2009;Chevignard et al, 2017;Doger de Sp eville et al, 2018;Edelstein et al, 2011;King et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances to the development of networks not only occur in survivors of pediatric brain tumors (Chen et al, 2016;Na et al, 2018) but also affect children with cancers outside the CNS such as leukemia and lymphoma (Kesler et al, 2014(Kesler et al, , 2016. Leukemia and its potentially neurotoxic therapy might disrupt the functional and structural development of the brain (Hearps et al, 2017).…”
Section: Introductionmentioning
confidence: 99%